Enduring problems in the offspring of depressed parents followed up to 38 years. (August 2021) - Weissman, Myrna M.; Talati, Ardesheer; Gameroff, Marc J.; Pan, Lifang; Skipper, Jamie; Posner, Jonathan E.; Wickramaratne, Priya J.
Abstract: Background: while the increased risk of major depressive disorder (MDD) in offspring of depressed parents is one of the best-replicated findings in psychiatry, their long-term outcomes are less well known. The clinical outcomes of biological offspring of depressed (high-risk) and not depressed (low-risk) parents who have been directly interviewed over the years are presented. Methods: a longitudinal retrospective cohort study began in 1982, and 276 biological offspring of moderately-to-severely depressed or non-depressed parents from the same community were followed up to 38 years. Rates of psychiatric disorders for offspring were collected by clinically trained interviewers. Final diagnoses were made by M.D. or Ph.D. clinicians. Mortality and cause of death were obtained from relatives and registries. Findings: high- compared to low-risk offspring continue to have about a three-fold increased risk of MDD, increased rates of anxiety disorder, substance dependence, and poorer functioning over the life course. Adolescence and early adulthood remain prime age of first onsets. Within high-risk group only, the death rate due to unnatural causes, suicides and overdose was 4·97/100 in the offspring and 5·36/100 in their parents. This subsample of White, lower-educated, often unemployed persons, who died by unnatural causes are similar demographically to those described as having a recent increase in 'deaths of despair'. Interpretation: family history of MDD continues to be a powerful predictor of clinical course and mortality and should be probed in clinical visits, especially in youth when depression usually first appears. Funding: This work is supported by NIMH grant R01MH-036, 197 (P.I.s: Weissman, Posner).